Two lives - Seth, Vikram, 1952- (HarperCollins, 2005)
Shanti Behari Seth, brought up in India, was sent by his family in the 1930s to Berlin--though he could not speak a word of German--to study medicine and dentistry. Helga Gerda Caro, known to everyone as "Henny" was also born in 1908, in Berlin, to a Jewish family--cultured, patriotic, and intensely German. When the family decided to take Shanti as a lodger, Henny's first reaction was, "Don't take the black man!" But a friendship flowered, and when Henny fled Germany just one month before war broke out, she was met at Victoria Station by the only person in the country she knew: Shanti. Vikram Seth has woven together their story, which recounts the arrival into this childless couple's lives of their great-nephew from India--the teenage Vikram. The result is a tapestry of India, the Third Reich and the Second World War, Auschwitz and the Holocaust, Israel and Palestine, postwar Germany and 1970s Britain.--From publisher description.